Context-Dependent Neural Modulations in the Perception of Duration - Murai, Yuki; Yotsumoto, Yuko (Frontiers in Integrative Neuroscience, 2016)
Recent neuroimaging studies have revealed that distinct brain networks are recruited in the perception of sub- and supra-second timescales, whereas psychophysical studies have suggested that there are common or continuous mechanisms for perceiving these two durations. The present study aimed to elucidate the neural implementation of such continuity by examining the neural correlates of peri-second timing. We measured neural activity during a duration reproduction task using fMRI. Our results replicate the findings of previous studies in showing that separate neural networks are recruited for sub- versus supra-second time perception: motor systems including the motor cortex and the supplementary motor area for sub-second perception, and the frontal, parietal, and auditory cortical areas for supra-second perception. We further found that the peri-second perception activated both the sub- and supra-second networks, and that the timing system that processed duration perception in previous trials was more involved in subsequent peri-second processing. These results indicate that the sub- and supra-second timing systems overlap at around 1 second, and cooperate to optimally encode duration based on the hysteresis of previous trials.